(untitled) (Research, Society and Development, 2021)
The açai is a palm tree native to the Amazon. Despite the economic potential currently presented by this species, there are still few studies related to the development of this plant in the face of water deficits. This work aimed to evaluate the growth and development of young açaí palm plants in an Oxisol under different water stress levels. The experiment was carried out in an greenhouse located at the Federal Rural University of Amazônia, Campus de Capitão Poço. The treatments were arranged in a completely randomized design with the following treatments: daily irrigation with soil moisture maintained between 80 to 85% of field capacity (control); suspension of irrigation for 3 days; 7 days; 14 days and 21 days. Plant height, stem diameter, number of leaves and leaflets, leaf area, root length and volume, relative water content, dry mass and biomass allocations in different vegetative parts were evaluated. The 21-day irrigation interval provided lower seedling responses for most of the analyzed variables. The water deficit caused higher accumulation of root dry mass and higher allocation of biomass in the root. Thus, the water deficit negatively influenced the development of açaí palm seedlings.